2014
DOI: 10.1589/jpts.26.105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Walking Program on Self-management and Risk Factors of Metabolic Syndrome in Older Korean Adults

Abstract: [Purpose] The aim of this study was to determine the effects of a 12-week walking program on increasing an individual’s self-management and decreasing the risk factors of metabolic syndrome in the older adult population. [Subjects] A total of 31 older adults participated in this study. Eighteen participants in the experimental group and 13 controls completed the pretest and posttest measures. A walking exercise and health education were provided for the experimental group. Data were analyzed by ANCOVAs to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
(21 reference statements)
1
16
0
Order By: Relevance
“…To our knowledge, the present study is the first intervention study to examine the relationships between exercise and measures of muscle mass of the limbs in obese elderly women. This study also reconfirmed the results of previous studies which found that the effect of exercise on cardiovascular risk factors in this population 23 , 24 ) .…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, the present study is the first intervention study to examine the relationships between exercise and measures of muscle mass of the limbs in obese elderly women. This study also reconfirmed the results of previous studies which found that the effect of exercise on cardiovascular risk factors in this population 23 , 24 ) .…”
Section: Discussionsupporting
confidence: 90%
“…Worksite health promotion programs for MetS have been reported to achieve substantial risk reduction [53,54]. Prevention and treatment [55] of the predictive factors together with enhanced lifestyle-modification [56,57] and intervention [58] may jointly reduce the prevalence of MetS risk factors [59]. A good example of significant decreases in MSC (from 2.1 down to 1.1) can be found in a study of subjects who completed a weight loss program [60]; similarly, for many health conditions, it is worthwhile to put associations; hence, some potential limitations of our analysis need to be considered.…”
Section: Metabolic Syndrome Component Count and Shift Work O R I G I mentioning
confidence: 99%
“…Moreover, the frequency of this syndrome is increased in developed countries, sedentary people, smokers, low socioeconomic status population, as well as in individuals with unhealthy dietary habits [29,30]. …”
Section: The Metabolic Syndromementioning
confidence: 99%